Bacteria in agrobiology plant nutrient management - Maheshwari, Dinesh K. (Springer eBooks., 2011)
The future of agriculture strongly depends on our ability to enhance productivity without sacrificing long-term production potential. An ecologically and economically sustainable strategy is the application of microorganisms, such as the diverse bacterial species of plant growth promoting bacteria (PGPB). The use of these bio-resources for the enhancement of crop productivity is gaining worldwide importance. ?Bacteria in Agrobiology: Plant Nutrient Management? focus on the management of plant nutrient to support plant growth and development. The topics treated in this book include mechanisms of plant growth promoting rhizobacteria, zinc and phosphate solubilizing microorganisms, sulfur oxidizing bacteria, ACC deaminase, siderophores, phytohormones, quorum-sensing, biofilms, antibiotics, volatiles, denitrification and integrated nutrient management